Socio Economic Status of Deo/Dev Community in Nepal - Deo, Sachindra Kumar (NPRC Journal of Multidisciplinary Research, 2026)
Background: During the age of Vidyapati (fourteenth-fifteenth centuries AD), Mithila reflected a highly sophisticated cultural and intellectual region characterized by unique socio-cultural structures. Gradually, various groups, such as the Dev group (with subgroups like Bisahariya) of Nepal, have been marginalized due to their caste. Present-day policy frameworks, such as the GESI Strategy (2021-2023) in Nepal, attempt to rectify historic inequalities. Nevertheless, there is still limited knowledge concerning the relationship between historic socio-cultural formation and current exclusion. Purpose: This paper aims to compile information from both historic and present-day resources to (a) describe the socio-cultural context of Mithila in the age of Vidyapati, (b) outline the historic journey of the Dev caste of Nepal, and (c) assess present-day GESI policy approaches towards addressing caste and gender-based exclusion. Methods: A qualitative content analysis of secondary data sources was conducted using Radhakrishna Chaudhary’s "Mithila In The Age Of Vidyapati" (1976), Ramkrishna & Roopali Mukherjee’s "Rise and Fall East India" (1974), the GESI Strategy 2021-2023 of the Government of Nepal, Gender Equality and Social Inclusion Strategy by Rai & Sharma (2021), Deepak Chaudhary’s "Dev Community of Nepal: A Case Study of Bisahariya VDC" (2012), and Ram Narayan Deo’s "Dev Jatiko Itihas" (2017). Conclusions: The Mithila era during the reign of Vidyapati witnessed the presence of advanced literature and ritual practices along with existing hierarchies within the caste system. The Dev people group, which includes Bisahariya, have been socio-economically marginalized in Nepal and remain underrepresented in general discourse. The current GESI initiatives are well-intentioned and comprehensive; however, there is a lack of action concerning excluded castes. Conclusions: Social hierarchies established during ancient times in Mithila can still be seen today through marginalization of certain communities, such as Dev people group, in contemporary society. Although GESI initiatives (2021-2023) exist, focused efforts on particular communities that take into account past and present research are crucial.